Privacy-enhancing technologies for CBDC solutions - Rakesh Arora; Han Du; Raza Ali Kazmi; Le; Duc-Phong (Bank of Canada, 2025)
With the rapid digitization of financial transactions, central banks have given considerable focus in recent years to the research and development of central bank digital currencies (CBDCs). While CBDCs could offer several advantages, there are concerns about end-user privacy. Traditional methods of protecting confidentiality in banking and financial systems have primarily relied on data encryption and access control techniques. However, these techniques alone are inadequate, especially in cases where data are shared across different entities because privacy in such situations is typically governed by legal frameworks. Privacy-enhancing technologies (PETs) can offer robust protection for data throughout their lifecycle, whether stored, in transit or during processing, and ensure privacy is maintained even when data are extensively shared or analyzed. This study explores the use of PETs in the design of CBDC systems, potentially paving the way for solutions that better safeguard end-user privacy and meet rigorous data protection standards. While PETs promise significant advancements in privacy protection, they present some challenges in implementation. They can introduce performance overheads and add complexity to systems, and their effectiveness and applicability are currently limited due to their early stage of development. As these technologies evolve, it is crucial for organizations to carefully consider these factors to fully leverage PET benefits while managing associated challenges. This paper provides a comprehensive overview of how PETs can transform privacy design in financial systems and the implications of their broader adoption.
Keywords: E; E4; E42; O; O3; O31; 330; Central bank research; Digital currencies and fintech; Financial system regulations and policies; Payment clearing and settlement systems